Optimal Size for Utilities? Returns to Scale in Water: Evidence from Benchmarking - Tynan, Nicola (World Bank, Washington, DC, 2012)
Using data from 270 water and sanitation providers, this Note investigates the relationship between a utility's size and its operating costs. The current trend toward transferring responsibility for providing services to the municipal level is driven in part by the assumption that this will make providers more responsive to customers' needs. But findings reported here suggest that smaller municipalities may face higher per-customer costs and could lower costs (and prices for consumers) by merging.